Mastering Workplace English: A Book Review of 'English for Business Communication' by Mable Chan - MOFFATT, Piangchan; UKE, Waode Ade Sarasmita (Research and Innovation in Applied Linguistics, 2023)
Although business English books have been extensively published during the last two decades (Bhatia & Bremner, 2012; Emmerson, 2010; Sweeney, 2003; Talbot, 2009), this book, "English for Business Communication" by Mable Chan (2020), is a comprehensive textbook designed for students and professionals studying English for business or workplace communication. It covers both spoken and written English and incorporates up-to-date research in business communication. The book focuses on the realities of communication in the business world today, including the use of English in social media and the concept of communicative competence. It also includes analysis of email communication, informal English, and English for socialization. Additionally, the book explores persuasive messages and provides an e-resources website with authentic workplace genres and relevant research studies.